2022
DOI: 10.1109/access.2022.3186753
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Fault Diagnosis for BLDC With Incorporating Accuracy and False Negative Rate in Feature Selection Optimization

Abstract: Early fault diagnosis is essential for the proper operation of rotating machines. This article proposes a fitness function in differential evolution (DE) that considers accuracy rate and false negative rate for optimization in brushless DC (BLDC) motor fault diagnosis. Feature selection based on a distance discriminant (FSDD) calculates the feature factors which base on the category separability of features after the Hilbert-Huang transform (HHT) which extracts the features of four different type signals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the past two decades, the AFPMBLDCs have been widely researched throughout the world. In [3,4], we found that the AFPMBLDC can provide a larger output torque compared with the radial flux brushless DC motor. However, the torque ripple cannot be neglected due to the high cogging torque.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the past two decades, the AFPMBLDCs have been widely researched throughout the world. In [3,4], we found that the AFPMBLDC can provide a larger output torque compared with the radial flux brushless DC motor. However, the torque ripple cannot be neglected due to the high cogging torque.…”
Section: Introductionmentioning
confidence: 94%
“…Polar arc coefficient 0.6-0.9 Permanent magnet thickness 2.0-3.5 permanent magnet arc radius 18-24 Air-gap length 0.5-1.5 Based on the four variable optimization parameters selected above, a range of four level factors were determined for each parameter, an orthogonal table was established. If the traditional single-variable optimization method was used; 4 4 = 256 experiments are required, while only 4 × 4 = 16 experiments are required to achieve the multivariable and multi-objective optimization design of the motor using Taguchi's method. The orthogonal table for establishing experiment L16(4 × 4) is shown in Table 4.…”
Section: Parameter Valuementioning
confidence: 99%
“…Permanent Magnet Synchronous Motors (PMSMs) are widely applied in industrial applications and have been comprehensively improved through the development of outstanding features such as high efficiency, low noise, and small volume [1,2]. In recent decades, PMSMs and Brushless Direct Current motors (BLDCMs) have been preferred for LEV applications by manufacturers due to their advantages such as high performance, ease of manufacture and regenerative braking capability [3,4]. BLDCMs are obviously a type of PMSM.…”
Section: Introductionmentioning
confidence: 99%